Light-microscopy methods in C. elegans research. Issue 13 (February 2019) - Breimann, Laura; Preusser, Friedrich; Preibisch, Stephan
Abstract: Ever since Caenorhabditis elegans was introduced as a model system it has been tightly linked to microscopy, which has led to significant advances in understanding biology over the last decades. Developing new technologies therefore is an essential part in the endeavor to gain further mechanistic insights into developmental biology. This review will discuss state-of-the-art developments in quantitative light microscopy in the context of C. elegans research as well as the impact these technologies have on the field. We will highlight future developments that currently promise to revolutionize biological research by combining sequencing-based single-cell technologies with high-resolution quantitative imaging. Graphical abstract: Image 1